2016
DOI: 10.1007/s40964-016-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural design of Ni-base alloys for high-temperature applications: impact of heat treatment on microstructure and mechanical properties after selective laser melting

Abstract: Optimising the microstructure and mechanical performance of Ni-base alloys is vital to achieve higher efficiencies in many high-temperature applications. With the recent emergence of the additive manufacturing technologies, new possibilities with respect to freedom of design and microstructure manipulation are opened up. This study aims at adjusting a microstructure suited for high-temperature applications by employing high-power selective laser melting. The parts are subjected to diverse post-process heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 36 publications
6
28
1
1
Order By: Relevance
“…This kind of as built microstructure with the presence of Laves phases and carbides at different locations is also reported in other studies . Brenne et al also identified Laves phases in the as built state of SLM Inconel 718 using EDS and TEM techniques …”
Section: Resultssupporting
confidence: 79%
“…This kind of as built microstructure with the presence of Laves phases and carbides at different locations is also reported in other studies . Brenne et al also identified Laves phases in the as built state of SLM Inconel 718 using EDS and TEM techniques …”
Section: Resultssupporting
confidence: 79%
“…16), have been reported many times. This microstructure evolution has been reported for various alloys, e.g., Ni-based superalloy IN 718, [17][18][19][20][21][22] aluminum alloys, 23 the primary bcc b-phase in Ti-6Al-4V, 24,25 and several austenitic steels processed by L-PBF 26 and EBM. 27 Evolution is mainly attributed to the principal heat flux alongside BD and the favorable h100i growth direction in cubic crystal systems, due to an anisotropy in the solid-liquid interface energy.…”
Section: Introductionsupporting
confidence: 72%
“…It is important to note that both the Laves phase and the hardening phases γ and γ" consume niobium for their formation. The dissolution temperature of the Laves phase is between 982 and 1093 • C [43], while γ and γ" precipitates form during the cooling phase at about 900 • C [44]. As already detailed above, it can be concluded that during the build, the temperatures within the strut deviated significantly from the bulk, eventually leading to the different appearance of the microstructure within the struts.…”
Section: Microstructurementioning
confidence: 72%